2014
DOI: 10.4236/abb.2014.54044
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Regeneration of <i>Curcuma caesia</i> Plantlets from Basal Part and via Somatic Embryogenesis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…All the successful induction of callus in this study were obtained in 2, 4-D + BAP supplemented MS media. 2, 4-D alone failed to induce calluses at all the concentration tested (0.5, 1….3 mg/L) which was in line with the report of Zuraida et al, (2014) in C. caesia and also with the finding of Miachir et al, (2004) and Tuan et al, (2011) in C. zedoaria, however, in contradiction to the finding of Saensouk, (2011) were similar and differed from all others (p <0.05). Equal and higher concentration 2,4-D + BAP of 5 mg/L each, responded well (40.00%) to callus induction in contrast to the finding of Taha et al, (2013) who reported higher concentration of 2,4-D up to 4 mg/L in combination with 0.2 mg/L BAP to have performed less in the in vitro culture of Zingiberofficinale using leaves explants.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…All the successful induction of callus in this study were obtained in 2, 4-D + BAP supplemented MS media. 2, 4-D alone failed to induce calluses at all the concentration tested (0.5, 1….3 mg/L) which was in line with the report of Zuraida et al, (2014) in C. caesia and also with the finding of Miachir et al, (2004) and Tuan et al, (2011) in C. zedoaria, however, in contradiction to the finding of Saensouk, (2011) were similar and differed from all others (p <0.05). Equal and higher concentration 2,4-D + BAP of 5 mg/L each, responded well (40.00%) to callus induction in contrast to the finding of Taha et al, (2013) who reported higher concentration of 2,4-D up to 4 mg/L in combination with 0.2 mg/L BAP to have performed less in the in vitro culture of Zingiberofficinale using leaves explants.…”
Section: Resultssupporting
confidence: 85%
“…The earliest result was obtained in the 5th week of culture in 2,4-D 0.5 mg/l +BAP 0.1 mg/L, and 2,4-D (0.5 mg/L) + KIN (0.1 mg/L) combinations followed by 2,4-D and BAP (5.0 mg/L each) in the 6th week and 2,4-D (1.0 mg/L) + BAP 0.5 mg/L) and IAA (2.0 mg/L) + BAP (1.0 mg/L) in the 8th week of inoculation. All the responses in term of a number of days from a culture obtained in this study were earlier than what was obtained from C. caesia inoculated on woody plant medium supplemented with 2.0 mg/L 2,4-D + 5.0 mg/L BAP (20%) as reported by Zuraida et al,(2014) where the best callus (20%) was achieved after 70 days of culture.…”
Section: Resultssupporting
confidence: 46%
“…Therefore, somatic embryos have potential applications for large-scale production of turmeric plants. Zuraida et al (2014) showed that a culture medium supplemented with 5 mg/l BAP and 2 mg/l 2,4-D enhanced callus induction after 70 days of culture, and that somatic embryogenesis was most successful with MS medium supplemented with 6.0 g/l agar, 5 mg/l BAP and 0.2 mg/l 2,4-D, obtaining 53% of calli differentiation into green somatic embryos and consequently a large number of plantlets. However, since callus formation causes somatic variation and the regenerated plants are not genetically uniform, in vitro screening is necessary.…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…Genotype and source of explants would influence the production of embryogenic calli and also the regenerated plantlets [20]. Many reports on successful embryogenic callus induction in many plant species using 2,4-D and BAP hormone have been reported [21]- [24].…”
Section: Introductionmentioning
confidence: 99%